Episodic Variability of Gamma Rays in Quasar 3C 273 Based on Fermi-LAT Statistical Analysis - Ruben Cornelius Siagian (Politeknik Negeri Medan, 2026)
Quasar 3C 273 is one of the brightest quasars, known for its active core and relativistic jets that produce intense gamma-ray emissions. This study aims to analyze the gamma-ray variability of 3C 273 using Fermi-LAT data (0.1–300 GeV), detect episodic flares, and understand the physical mechanisms in the quasar core. Data were collected through Xamin Search at coordinates J2000 RA = 187.278° and Dec = 2.052°, cleaned of observations with offsets >0.05° or missing flux, then analyzed for average flux, standard deviation, variance, fluctuation amplitude, and gamma-ray luminosity. Flares were identified as flux >2σ above the average, while periodicity was tested using the Lomb-Scargle periodogram. Results show that from 1,212 observations, the average flux was 6.22 × 10⁻⁷ ph/cm²/s with a standard deviation of 4.53 × 10⁻⁷ ph/cm²/s, and a fluctuation amplitude of 4.90 × 10⁻⁶ ph/cm²/s. Thirty-eight flares (>2σ) were detected during 3.14% of the observation time. The periodogram showed a broad power distribution without any apparent periodicity, confirming the stochastic variability dominated by sporadic flares. This study closes the gap in the quantification of episodic gamma-ray flares with systematic statistical analysis. In conclusion, 3C 273 exhibits significant variability and sporadic flares, consistent with the relativistic jet and accretion instability models. The novelty of this study is the integration of quantitative analysis of gamma-ray fluctuations to systematically assess the dynamics of the quasar core.